HUBUNGAN WORK-LIFE BALANCE DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN RADIO CLASSY FM PADANG - Bantar, Genia Yevandrest; Nio, Suci Rahma (CAUSALITA : Journal of Psychology, 2023)
This study aims to look at the relationship between work life balance and organizational citizenship behavior on employees of Radio Classy FM Padang. This study uses a quantitative method with a correlational approach. The population in this study are all employees of Radio Classy FM Padang. Researchers used a total sampling technique, amounting of 33 respondences. The instrument in this study uses the work life balance scale and organizational citizenship behavior scale which have been tested for validity and reliability based on previous research. The work life balance scale is the scale developed by Disti (2018) based on Fisher, Bulger, and Smith (2009). Meanwhile, the organizational citizenship behavior is a scale developed by Dewi (2021) based on Organ (1994). Data analysis was performed using product moment analysis with SPSS 21 for windows and a correlation coefficient (r) = 0.507 was obtained with a significance value of p = 0.003 (p <0.05), meaning that there is a positive relationship between work life balance and organizational citizenship behavior. Where it can be concluded that the greater the work life balance, the greater the occurrence of organizational citizenship behavior in employees.